Mental Disorders with A Risk for Violent Behavior Who Have Risky Behaviors and Tend to Smoke: a Case Study - Indriyawati; Alfiyanto, Ahmad Guntur; Ulfa, Miftakhul (Jurnal Kesehatan Komunitas Indonesia, 2023)
Smoking behavior in patients with mental disorders is known as a risk factor and can affect one aspect of treatment and change in behavior. In addition, smoking will also stimulate psychiatric symptoms and more severe symptoms of recurrence. The objective is to determine the extent of the impact or influence of smoking behavior on mental disorder patients with a risk of violent behavior who have risky behavior tending to smoke in Bantur Health Center. The method used in this research is a case study approach using qualitative and quantitative descriptive research types. This study involved 3 respondents. Data collection is based on interviews, observation, and documentation according to the format of mental nursing care. The results of the study showed that respondents were able to perform nursing actions in generalist nurse therapy sessions 1-5. In the final stage of the study, the results showed that the three patients experienced changes in behavior by being able to practice and mention interventions in each session, but had not been able to reduce smoking behavior because the three patients had been active smokers since they were teenagers. The conclusion from this study is that smoking behavior is a risk factor for pople with mental disorders, especially in behavior. Generalist ners therapy sessions 1-5 for respondents with the risk of violent behavior resolved well, but not for smoking behavior because it takes longer and requires several processes and a stronger desire. It is hoped that future researchers can increase research time in the care process to approach the family in carrying out nursing care not only for the patient but also for the patient's family.